Educating Refugees to the Welfare State: Educational Social Integration and Language Education in the Danish Refugee Council from the late 1960s to the 1980s - Bergenheim, Sophy (Nordic Journal of Educational History, 2026)
This article explores the development of educational knowledge on integrating refugees to the Danish welfare state, conceptualised as “educational integration knowledge”. The topic is studied by analysing the Danish Refugee Council’s (DRC) educational social integration and language education for refugees ca. 1968–85, a period of increasing immigration and welfare state expansion, with which DRC’s development intertwined. The article examines how DRC developed educational integration knowledge in relation to its encounters with refugee groups, as well as changing circumstances in the welfare state. It was a two-way process entailing education both for and about refugees. Initially, DRC had pioneering autonomy to implement and develop its educational integration knowledge in the welfare state’s margins. However, the expanding and consolidating welfare state brought about increasingly rigid regulatory structures and efficiency requirements, respectively diminishing DRC’s autonomy.